Studies in hypersonic viscous interactions - Murthy, A. V. (Cranfield University, 1972)
The literature on the leading edge viscous interaction phenomena has "been reviewed. Theoretical studies of the leading edge bluntness and the boundary - layer displace¬ment effects have been made by using a combination of tangent wedge + centrifugal force pressure law relation and also using the 2nd order tangent wedge formula suggested by Lees . These analyses, when applied to concave surfaces show a mild oscillatory behaviour compared to the highly oscillatory results of Cheng's theory. Further, an integral approach due to Chernyi has been applied to concave surface flows and the damping of the oscillations present in Cheng’s theory is demonstrated. Experiments have been conducted at a Mach number Of 1 2 .2 in a gun tunnel, on flatplates and on a concave surface with a sharp leading edge. The results are compared with the predictions of various interaction theories.